Mengenal Multi Dimensional Scaling - Muhammad Idrus (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2006)
Measurement of psychological attributes is an important aspect in Psychology. Related with that, the application of measurement tools-including tests scaling become important. So far, Most of psychological scales apply uni-dimensional scaling model which  is not sufficient to measure double or even multi-dimension of psychological attributes basically. Therefore, it is necessary to apply multidimensional scaling model in psychological measurement. Multidimensional Scaling (MDS) is a method to represent distance distinction of similarity or unsimiliarity between objects. MDS interlace with the situations where the stimulus is various with some dimensions simultaneously. Some methods in MDS including: the method of triads, complete methods of triads, the methods of tetrads, the method of multidimension rank-order, the method of multidimensional successive categories and the method of confusion.Keywords: Multidimensional scaling, uni-dimensional scaling